The determination of potential evapotranspiration based on data UMP weather station - Wan Mohd Zainuddin, Wan Ismail (2010)
Potential evapotranspiration (PET) is an important index of hydrologic budgets at different spatial scales and is a critical variable for understanding regional biological processes. It is often an important variable in estimating actual evapotranspiration (AET) in rainfall-runoff and ecosystem modeling. However, PET is defined in different ways in the literature and quantitative estimation of PET with existing mathematical formulas produces inconsistent results. The objectives of this study were to determine the potential evapotranspiration using the penman procedure based on Hydrological Procedure 17 (HP 17 1999) and compare it with the interpolation map produced by the Meteorology Malaysian Department (MMD). The studied found that PET values calculated were favorably within the interpolation value (3.5 to 4.00). Based on the criteria of availability of input data and the value of PET computed from the Universty Malaysia Pahang (Ump) weather station are suggested in the future as one of the weather station or for validation.